Mechanical properties of oil palm fibre-reinforced polymer composites: a review - Asyraf M.R.M.; Ishak M.R.; Syamsir A.; Nurazzi N.M.; Sabaruddin F.A.; Shazleen S.S.; Norrrahim M.N.F.; Rafidah M.; Ilyas R.A.; Rashid M.Z.A.; Razman M.R. (Elsevier Editora Ltda, 2023)
Biodegradability; Biodegradable polymers; Fiber reinforced plastics; Fibers; Fracture toughness; Impact strength; Palm oil; Reinforcement; % reductions; Biocomposite; Fiber reinforced polymer composites; Flexural properties; Impact toughness and biocomposite; Lignocellulosic fibres; Mechanical performance; Oil palm; Oil palm fibres; Petroleum resources; Biopolymers